2019
DOI: 10.1007/s13318-019-00591-7
|View full text |Cite
|
Sign up to set email alerts
|

High Variability of Whole-Blood Tacrolimus Pharmacokinetics Early After Thoracic Organ Transplantation

Abstract: Background and Objective Oral tacrolimus is initiated perioperatively in heart and lung transplantation patients. There have been few studies on oral tacrolimus pharmacokinetics early post-transplantation, even though tacrolimus-related toxicity may occur early, potentially leading to morbidity and mortality. Therefore, we aimed to study the pharmacokinetics of oral tacrolimus in thoracic organ recipients during the first days after transplantation. Methods We conducted a pharmacokinetic study in 30 thoracic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 60 publications
(79 reference statements)
1
28
1
1
Order By: Relevance
“…43 Additionally, in the first week after heart transplant, approximately 95% of transplant recipients in this study received high doses of a proton pump inhibitor, which may reduce the absorption of itraconazole 44 and thereby contribute to a variability in the effect of drugdrug interaction on tacrolimus pharmacokinetics. Consistent with other studies, 1,45 the present study (Table 3) demonstrated that the dynamic physiological changes that occur in heart transplant recipients in the first 1-2 weeks after transplant make predicting tacrolimus drug exposure during this period very difficult. Further work is required to examine whether these temporal changes can be systematically quantified to improve the prediction of tacrolimus concentrations using the Bayesian software during the first 11 days of tacrolimus therapy.…”
Section: Discussionsupporting
confidence: 88%
“…43 Additionally, in the first week after heart transplant, approximately 95% of transplant recipients in this study received high doses of a proton pump inhibitor, which may reduce the absorption of itraconazole 44 and thereby contribute to a variability in the effect of drugdrug interaction on tacrolimus pharmacokinetics. Consistent with other studies, 1,45 the present study (Table 3) demonstrated that the dynamic physiological changes that occur in heart transplant recipients in the first 1-2 weeks after transplant make predicting tacrolimus drug exposure during this period very difficult. Further work is required to examine whether these temporal changes can be systematically quantified to improve the prediction of tacrolimus concentrations using the Bayesian software during the first 11 days of tacrolimus therapy.…”
Section: Discussionsupporting
confidence: 88%
“…The study by Sikma et al showed further that the majority of C12h, almost 70%, were out of the target range (9-15 ng/mL). Half of the patients displayed subtherapeutic concentrations and approximately 20% of patients displayed supratherapeutic concentrations [28]. Moreover, the interoccasion (dose-to-dose) variability in pharmacokinetics was extreme and exceeded the interpatient variability [29].…”
Section: Interoccasion Variability In Tacrolimus Pharmacokineticsmentioning
confidence: 99%
“…Tacrolimus values from POD21 onward were used to calculate IPV to eliminate initially high variability seen in the postoperative phase of care. 12 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Tacrolimus values from POD21 onward were used to calculate IPV to eliminate initially high variability seen in the postoperative phase of care. 12,18 The Rosendaal linear interpolation method was used to calculate TTR, which assumes a linear relationship exists between each measured value and then assigns a specific value for each day between tests. 19 Protocol tacrolimus goals were used to calculate 12-month TTR.…”
Section: Tacrolimus Level Assessmentmentioning
confidence: 99%